PERJALANAN DAKWAH KH. ZAHRUDIN USMAN DALAM PENGEMBANGAN SYIAR ISLAM DI KABUPATEN TEBO PROVINSI JAMBI - Sari, Sinta Kartika (Jurnal Dakwah, 2020)
KH. Zahrudin Usman is a prominent Muslim intellectual figure. Thanks to his expertise, he got the title of youth officer and several awards. This study seeks to explain KH Zahrudin Usman's preaching work in the development of Islamic symbols in Tebo Regency, Jambi Province. This research is a qualitative research with historical literature sources supported by data from the field both interviews and observations to corroborate the findings. The findings of this study indicate that KH Zahrudin Usman is a Kyai who has great authority in the development of Islamic symbols through the Nurul Jalal Islamic boarding school in Tebo Tengah, Tebo Regency, Jambi Province. The existing knowledge is implemented by establishing a madrasah which is used as a place for learning. It is not just its existence, its method of preaching, and its moral message as a barometer to become a role model for the people of Tebo Regency.KH. Zahrudin Usman merupakan tokoh intelektual Muslim terkemuka.  Berkat kepiawaiannya, gelar mualim muda dan beberapa penghargaan didapatnya. Penelitian ini berusaha menjelaskan kiprah dakwah KH Zahrudin Usman dalam pengembangan syiar Islam di Kabupaten Tebo, Provinsi Jambi. Penelitian ini merupakan penelitian kualitatif dengan sumber literatur sejarah didukung data dari lapangan baik wawancara maupun observasi  untuk menguatkan hasil temuan. Adapun hasil  temuan dari penelitian ini adalah KH Zahrudin Usman merupakan Kyai yang memiliki otoritas besar dalam pengembangan syiar Islam melalui pesantren Nurul Jalal di Tebo Tengah, Kabupaten Tebo Provinsi Jambi. Bekal ilmu yang ada diimplementasikan dengan mendirikan madrasah yang dijadikan sebagai wadah pembelajaran. Bukan sekedar keberadaannya, metode dakwahnya, hingga pesan moralnya pun menjadi suatu barometer yang menjadi panutan masyarakat Kabupaten Tebo.